AB0185 Increased Corticotropin-Releasing Hormone (CRH) Expression in Cutaneous Lupus Lesions. (10th June 2014) - Schmitz, M.; Botte, D.C.; Bonfá, E.; Borba, E.F.; Mello, S.B.
Abstract : Background: Corticotropin-releasing hormone (CRH) and the pro-opiomelanocortin (POMC) axis activation leads to the production of several bioactive hormones such as adrenocorticotrophic hormone (ACTH) and the neuropeptide α-melanocyte stimulating hormone (α-MSH). In systemic lupus erythematosus (SLE), the prototype of autoimmune disease with a high frequency of skin involvement. There are no data concerning the possible role of CRH and MCs in the physiopathology of its cutaneous lesions. Objectives: Thus, the aim of the present study was to evaluate if CRH and POMC axis activation underlies the cutaneous inflammatory response in SLE patients Methods: Seventeen SLE patients were clinically evaluated and biopsies from affected and unaffected skin were compared to 17 healthy subjects. Immunohistochemical analysis for CRH, ACTH, a-MSH, and MC-1R were performed. Cytokine serum levels (IL-1, IL-1Ra, IL-6, IL-10, IL-12p70, IL-17, TNF-a, IFN-γ) was evaluated by multiplex bead-based immunoassay. Results: Interestingly, affected skin of SLE patients exhibited higher CRH expression in the deep dermis compared to controls (figure, p=0.024), in contrast, no difference regarding CRH expression in the epidermis was observed comparing affected and unaffected skin of SLE patients and health skin (p=0.353). Tissue expression of ACTH, cortisol, a-MSH and its receptor MC-1R were comparable in SLE and controls. Significantly higher serum levels of IFN-g (p=0.041), TNF-a (p=0.001) and IL-6 (p=0.049) were observed in SLE while a-MSH serum levels were alike in both groups. Conclusions: The novel finding of elevated CRH expression solely in affected skin deep dermis supports the notion of a cutaneous local dysfunction of CRH-POMC axis in the pathogenesis of cutaneous SLE lesions. Acknowledgements: Supported by Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP #09/54549-8) Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1492